Co/Co9S8@S, N-doped porous graphene sheets derived from S, N dual organic ligands assembled Co-MOFs as superior electrocatalysts for full water splitting in alkaline media. (December 2016) - Zhang, Xian; Liu, Shengwen; Zang, Yipeng; Liu, Rongrong; Liu, Guoqiang; Wang, Guozhong; Zhang, Yunxia; Zhang, Haimin; Zhao, Huijun
Abstract: Here we report the synthesis of Co/Co9 S8 core-shell structures anchored onto S, N co-doped porous graphene sheets (Co/Co9 S8 @SNGS) from thiophene-2, 5-dicarboxylate (Tdc) and 4, 4ˊ-bipyridine (Bpy) dual organic ligands assembled Co-based metal-organic frameworks (Co-MOFs) in situ grown on graphene oxide sheets (Co-MOFs@GO) by a room-temperature solution reaction. S-containing Tdc and N-containing Bpy not only trigger the growth of Co-MOFs nanocrystals with a fixed S/N atomic ratio of 1:2.4 on GO sheets in the presence of Co 2+ in H2 O/NaOH system, but also provide S, N doping sources in the pyrolysis process of Co-MOFs to form Co/Co9 S8 core-shell structure and S, N co-doping in graphene. The results demonstrate that the obtained Co/Co9 S8 @SNGS at 1000 °C (Co/Co9 S8 @SNGS-1000) by pyrolysis of Co-MOFs@GO exhibits superiorly bifunctional catalytic activities of the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in 0.1 M KOH electrolyte, affording an overpotential of 290 mV for OER at a current density of 10 mA cm −2 and 350 mV for HER at a current density of 20 mA cm −2 . The OER activity of Co/Co9 S8 @SNGS-1000 is slightly better than that of commercial RuO2 catalyst, simultaneously, Co/Co9 S8 @SNGS-1000 also exhibits good HER activity. As electrode material for full water splitting in 0.1 M KOH solution, the Co/Co9 S8 @SNGS-1000 electrodes exhibit O2 and H2 generation efficiencies of 2.48 and 4.87 μmol min −1 respectively, at an applied potential of 1.58 V ( vs. RHE) under the given time range, affording nearly 100% Faradaic yield during electrocatalytic water splitting to produce O2 and H2 . Graphical abstract: Highlights: S, N dual organic ligands were used to construct Co-MOFs on GO sheets at room temperature. Co/Co9 S8 @S, N-doped porous graphene sheets were derived from Co-MOFs@GO. Co/Co9 S8 @SNGS-1000 demonstrated bifunctional catalytic activities of OER and HER.